Interview: The didactic in the initial teacher’s training in order to work in the basic education, with Ilma Passos Alencastro Veiga - Silva, Edileuza Fernandes (2022)
The interview, based on Ilma Passos Alencastro’s thoughts, discusses the Didactic in the initial teachers' training to qualify students as teachers to work basic education. Theoretical and practical issues are addressed that take up interviewee's experiences, studies, research, and productions about this discipline, which is part of the pedagogy field and that plays a central role in the didactic-pedagogical training at the undergraduate level. Didactic is a discipline that, in turn, has as its object the successful teaching of the students. The interviewee's answers addressed a long-lasting confrontation between theory and practice, not only in her academic training but also in her professional performance. This led to deep reflections on didactics in the teacher training field. Her reflections confirm the complexity of the teachers' training and the central role of the didactic over this process. Besides, it may conclude that it is necessary to rethink the way this discipline is carried out in undergraduate courses throughtout Brazil to make this process democratic with open and critical discussions. Its current challenge is the convergence towards an innovative Didactic based on the  Historical-Critical Pedagogy.